Seguimiento farmacoterapéutico en pacientes con trastorno disco lumbar y cervical con radiculopatía atendidos en un hospital de Iquitos, 2022 - Canayo Grandez, Karen Fiorella (2023)
Lumbar and cervical disc disorder with radiculopathy is pain that begins at the level of the spine and increases in those positions where the nerves or roots are dilated. The objective is to evaluate pharmacotherapeutic follow-up in patients with lumbar and cervical disc disorder with radiculopathy treated in the neurosurgery office, Hospital III- Iquitos, EsSalud 2022. The study is quantitative, quasi-experimental, prospective; the population was 65 and 36 patients respectively; The methodology used was pharmacotherapeutic monitoring, using the Morisky Green test for adherence to treatment and the Visual Analogue Scale to measure pain intensity. The results obtained in both pathologies indicated a greater proportion of female patients, predominance of ages between 27 to 59 years, PRM4 70.8% and PRM5 52.8%, therapeutic adherence increased from 20% to 66.7% in patients with lumbar disc disorders and from 55.6% to 77.8% in patients with cervical disc disorders with radiculopathy, obtaining a decrease in the intensity of severe to moderate pain. It is concluded that pharmacotherapeutic monitoring contributes to improving adherence to pharmacological treatment in patients with lumbar and cervical disc disorder with radiculopathy, allowing the intensity of pain to be reduced and improving the patient's quality of life.